trig

posted by .

solve this equation:

4x^3-4x^2+13x-6=0

note: that's suppose to be 4x to the third and 4x squared

  • trig -

    After several tries I found a factor

    (2x-1)(2x^2 - x + 6) = 0
    x = 1/2 or x = (1 ±√-47)/4 or (1 ±i√47)/4

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. math

    Still looking at how to solve these... Both are cubic polynomials?
  2. Algebra

    Can you pleas Solve the quadric equation step by step 4x square =13x+2 4x^2 = 13x + 2 subtract 13x and 2 from both sides 4x^2 - 13x - 2 = 0 Now use the quadratic formula, since it does not factor.
  3. MATH/ALGEBRA

    SOLVE: ã(4x+ 5) + 1 = 0 ã(4x+ 5)= -1 (ã(4x+ 5))squared= (-1)squared 4x + 5 = 1 I know I solve for x I get that x = 1 but my book states that x = -1 Please show me how this is true I don't understand what the term ã means. …
  4. Algebra

    Hello all - I would like to check my work on 2 problems. Solve by factoring : x^2-13x= -12 x^2-13x+12= -12 + 12 x^2-13x+12= 0 (x-1)(x-12)= 0 x = 1 , 12 Solve using the square root property: 2x^2-35=15 2x^2-35-15=0 2x^2-50=0 2(x-5)(x+5)=0 …
  5. math

    Solve each equation and leave the answer in simplest radical form. x squared+6x-9=0 n squared-2n+2=5 3y squared-4y-2=0 I never learned how to do this. Can you help me?
  6. math

    How do i find the area of a triangle? For example: A squared + b squared= c squared 8.5 squared + 6.4 squared= c squared 72.25 + 40.96= c squared 113.21=c squared 10.6400188=c even tho i thought this was the answer it is not because
  7. intermidate algebra

    Solve each equadratic equation by factoring. 6^2-13x-28 36-13x-28 -13x=-36+28 x=64/13 check this, correct if wrong
  8. Math

    Solve the following equation. 4.7 = 1.13x^2 Do i square root the 1.13x^2 first?
  9. Math

    Factor the polynomial P(x)=x^3-2x^2-13x-10. Then solve the equation P(x)=0. This is what I got: P(x)=(x+1)(x^2-3x-10) P(x)=(x+1)(x-5)(x+2) When it says solve the equation P(x)=0 does it means solve for x?
  10. Math

    Find the shortcut. Solve these problems. Then find and explain a shortcut method for finding the answer. 52(Squared) - 42 (squared) = 82 (Squared) - 72 (Squared) = 122 (Squared) - 112 (Squared) = 312 (Squared) - 302 (Squared) = 892 …

More Similar Questions